Endodontic treatment of mandibular molar with root dilaceration using Reciproc single-file system - Daniely Amorin Meireles; Mariana Mena Barreto Bastos; André Augusto Franco Marques; Lucas da Fonseca Roberti Garcia; Emílio Carlos Sponchiado, Júnior (Korean Academy of Conservative Dentistry, 2013)
Biomechanical preparation of root canals with accentuated curvature is challenging. New rotatory systems, such as Reciproc, require a shorter period of time to prepare curved canals, and became a viable alternative for endodontic treatment of teeth with root dilaceration. Thus, this study aimed to report a clinical case of endodontic therapy of root with accentuated dilaceration using Reciproc single-file system. Mandibular right second molar was diagnosed as asymptomatic irreversible pulpitis. Pulp chamber access was performed, and glide path was created with #10 K-file (Dentsply Maillefer) and PathFile #13, #16 and #19 (Dentsply Maillefer) up to the temporary working length. The working length measured corresponded to 20 mm in the mesio-buccal and mesio-lingual canals, and 22 mm in the distal canal. The R25 file (VDW GmbH) was used in all the canals for instrumentation and final preparation, followed by filling with Reciproc gutta-percha cones (VDW GmbH) and AH Plus sealer (Dentsply Maillefer), using thermal compaction technique. The case has been receiving follow-up for 6 mon and no painful symptomatology or periapical lesions have been found. Despite the difficulties, the treatment could be performed in a shorter period of time than the conventional methods.